RECONSTRUCTION OF VIRTUAL ENVIRONMENT USING CAD-VR APPROACH (Journal of Information and Communication Technology, 2003)
Virtual environment should be able to replicate real environment as realistically as possible. This paper proposes a design framework for constructing virtual environments using Computer-Aided Design (CAD) and Virtual Reality (VR) packages, or in short, the CAD-VR approach. This paper discusses the technical issues involved based on the experience in developing two prototype models of the Universiti Utara Malaysia Sports Complex and the Sultanah Bahiyah Library. The benchmark of the development is the compatibility of the three dimensional (3D) CAD models with VR packages. The CAD modelling issues that have been encountered throughout the development stages are also discussed for future guidelines.